1995
DOI: 10.2307/4052533
|View full text |Cite
|
Sign up to set email alerts
|

Urban Elites, 1850–1914: The Rule and Decline of a New Squirearchy?

Abstract: In recent decades, several historians, including myself, have argued that many nineteenth-century British urban elites were akin to a sort of new squirearchy. The intention of this article is to explore how far this idea enables us to better understand the role, power, and style of urban leadership, and the political, social, and economic context in which it existed. Given that the termination point is 1914, it also examines how much the notion has to say about political change in the rapidly expanding urban c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Rhodes' systematic and thoughtful work on central-local relations and sub-national government of the 1980s confirms the negotiated complexities of the relationship (Rhodes 1981(Rhodes , 1984(Rhodes , 1985(Rhodes , 1988. And, of course, there has been a long tradition of local government initiative, from the 'gas and water socialism' and 'urban squirearchy' of the late nineteenth century (Fraser 1976, Garrard 1995, Hunt 2004, to the Poplarism and Little Moscows of the 1920s and 1930s (Branson 1979, Macintyre 1980, to the municipal Labourism of Herbert Morrison's London County Council and the pragmatic Toryism of the shires (Donoghue andJones 2001, Bulpitt 1983), to the taken for granted municipal empires of the post-1945 period, nominally with delegated responsibility for education, council housing, and social service, but in practice defining the local welfare state (Cockburn 1977, Dearlove 1979, Keith-Lucas and Richards 1978. And alongside this long tradition of municipal activism of one sort or another has run an equally significant discourse -particularly within the Conservative Party -finding an expression in a language of 'local patriotism' (Cragoe 2007), in which the local has been explicitly counterposed to fears of socialist centralism.…”
Section: Uses and Meanings Of Localismmentioning
confidence: 99%
“…Rhodes' systematic and thoughtful work on central-local relations and sub-national government of the 1980s confirms the negotiated complexities of the relationship (Rhodes 1981(Rhodes , 1984(Rhodes , 1985(Rhodes , 1988. And, of course, there has been a long tradition of local government initiative, from the 'gas and water socialism' and 'urban squirearchy' of the late nineteenth century (Fraser 1976, Garrard 1995, Hunt 2004, to the Poplarism and Little Moscows of the 1920s and 1930s (Branson 1979, Macintyre 1980, to the municipal Labourism of Herbert Morrison's London County Council and the pragmatic Toryism of the shires (Donoghue andJones 2001, Bulpitt 1983), to the taken for granted municipal empires of the post-1945 period, nominally with delegated responsibility for education, council housing, and social service, but in practice defining the local welfare state (Cockburn 1977, Dearlove 1979, Keith-Lucas and Richards 1978. And alongside this long tradition of municipal activism of one sort or another has run an equally significant discourse -particularly within the Conservative Party -finding an expression in a language of 'local patriotism' (Cragoe 2007), in which the local has been explicitly counterposed to fears of socialist centralism.…”
Section: Uses and Meanings Of Localismmentioning
confidence: 99%
“…Thereafter, in the transition period up to 1918, Garrard suggested that urban elites gradually withdrew from`active participation in the urban and industrial scene'. 42 However, the work of Doyle on Norwich in particular showed that this withdrawal did not always occur. Each town was different and in order to make progress in understanding the role of urban elites, it is necessary that there should be much more detailed interactional study on a range of towns and cities which represent as wide a diversity of urban categories as possible.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction in the frequency of large-scale funerals for local figures seems to have been part of a wider social and political shift in which urban elites gradually withdrew from civic politics and the consensus view is that civic rituals of almost all kinds experienced a perpetual decline. 77 This undoubtedly played a part in reducing the frequency of such events, something which has not been fully appreciated due to the lack of extensive historiographical consideration of public funerals. Yet it seems their decline was already underway, if they are viewed as public spectacle and a form of entertainment.…”
Section: Resultsmentioning
confidence: 99%